Samokontrol' v režime sportivnoj podgotovki detej 6-10 let - Iordanskaya, F. A.; Abramova, T. F. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The work is devoted to the substantiation of the use of self-control in the mode of sports training of 6-10-year-old children. Subjective and objective indicators of self-control are considered. Evaluation criteria have been determined that allow keepinga self-control diary. A comprehensive assessment of the subjective indicators of the body of children involved in sports sections allows, according to the sum of the revealed indicators, to determine an adequate level of tolerance to training loadsand timely recovery, promptly identify fatigue, sleep disorders, appetite, unwillingness to train, indicating the need to correct loads and health. Objective indicators of self-control make it possible to assess morphological and functional dynamic somatic and functional changes in accordance with the growth and development of the child`s body. Self-control diary for children of 6-10 years of age, involved in sports training in the chosen sport, is an important operational indicator of the adequacy of the plan and training program and the timely detection of violations requiring surgical preventive and pedagogical measures.Keywords:self-control, subjective and objective indicators, sports training of children 6-10 years old, self-control diary.